Envolvimento de mastócitos em um modelo de dor pós-operatória em camundongos - Oliveira, Sara Marchesan de (2012)
Recent studies have indicated that nearly half of all surgical patients present a picture of moderate to severe pain what become important to understand the mechanisms involved postoperative pain to be better treat it. Previous studies have shown that incisions can cause mast cell degranulation. Thus, the aim of this study was to investigate the involvement of mast cells and its inflammatory mediators, histamine, serotonin and tryptase in a model of postoperative pain in mice. The depletion of mast cell mediators produced by repeated pre-treatment with compound 48/80 (1, 3, 10 and 10 μg/paw), that promote mast cell degranulation, prevented postoperative nociception (98 ± 23% of inhibition) and reduced histamine and serotonin levels (88 ± 4% and 68 ± 10%, respectively) and tryptase activity (82 ± 14% of reduction) in paw tissue. Furthermore, plantar surgery produced immense mast cell degranulation, as assessed by histology and confirmed by the increased levels of serotonin (three fold higher) and histamine (fifteen fold higher) and by increased activity of tryptase (two fold higher) in the perfused tissue after surgery. Accordingly, pre-treatment with the mast cell membrane stabilizer cromoglycate (200 μg/paw, i.pl.) prevented mechanical allodynia (inhibition of 96 ± 21%) and an increase in histamine (44 ± 10% of inhibition) and serotonin (73 ± 5% of inhibition) levels and prevented the tryptase release (100% of inhibition) induced by plantar surgery. Finally, local treatment with H1 (promethazine, 100 μg/paw, i.pl.), 5-HT3 (ondansetron, 10 μg/paw, i.pl.), 5-HT2A (ketanserin, 5 μg/paw, i.pl.) or PAR-2 (ENMD-1068, 10-100 nmol/paw) receptor antagonists or with the tryptase inhibitor (gabexate, 0.01-1 nmol/paw) partially decreased postoperative nociception in mice. Thus, mast cell activation mechanisms as well as release of mast cells inflammatory mediators and activation of its respective receptors are interesting targets for the development of novel therapies to treat postoperative pain.